PENGARUH PENGGUNAAN METODE BERCERITA DENGAN TEKNIK MENDONGENG TERHADAP KECERDASAN LOGIKA-MATEMATIKA ANAK USIA 4-5 TAHUN DI TK AL-HIKMAH KEBRAON SURABAYA - Maulidiyah, Eka Cahya (IKIP PGRI MADIUN, 2013)
The aims of this research was to determine the presence or absence of the influence of applying storytelling method with narrating fairy tale technique toward mathematic-logic intelligence of children age 4-5 years in TK Al-Hikmah Kebraon Surabaya. This method is done by making children interested and happy on the material presented. The research was a pre-experimental design research through the One-Group Pretest-posttest design. Data collection technique was done by observation. The subjects of this research were 20 children of A3 group in TK Al-Hikmah Kebraon Surabaya.Techniques of data analysis is statistic non-parametric which is using Wilcoxon test marked level. From the calculation results obtained Tcount = 0 and Ttable = 52 so Tcount < Ttable. This means that the research hypothesis are acceptable.Keywords : storytelling method with narrating fairy tale techniques, mathematic-logic intelligence